Analisis Keuntungan Usaha Warung Makan Di Kawasan Objek Wisata Bukit Kasih Kanonang - Kasenda, Irene Maria; Mandei, Juliana Ruth; Pangemanan, Paulus Adrian (AGRI-SOSIOEKONOMI, 2023)
This study aims to find out how much profit is received from a food stall business in the Bukit Kasih Kanonang Tourism Object Area. This research will be carried out in September 2021 until it is finished, starting from preparation to preparing the report. The data collected in this study are primary data and secondary data. Primary data was obtained from interviews with respondents who run a food stall business using a questionnaire while secondary data was obtained from literature and previous research. The population in this study amounted to 4 food stall businesses. Sampling used the purposive sampling method, namely the collection of respondent data which was carried out deliberately by considering the respondent's criteria, namely food stalls that are still active and surviving today after the covid 19 pandemic. The results of the research conducted can be concluded that the average total cost incurred is Rp. 907,000 per month and with an income of Rp. 2,047,000 per month so that it can generate an average profit of Rp. 1,139,000.